Disruption of Epstein-Barr Virus Latency in the Absence of Phosphorylation of ZEBRA by Protein Kinase C - El-Guindy, Ayman S. (American Society for Microbiology, 2002)
ZEBRA protein converts Epstein-Barr virus (EBV) infection from the latent to the lytic state. The ability of ZEBRA to activate this switch is strictly dependent on the presence of serine or threonine at residue 186 of the protein (A. Francis, T. Ragoczy, L. Gradoville, A. El-Guindy, and G. Miller, J. Virol. 72:4543-4551, 1999). We investigated whether phosphorylation of ZEBRA protein at this site by a serine-threonine protein kinase was required for activation of an early lytic cycle viral gene, BMRF1, as a marker of disruption of latency. Previous studies suggested that phosphorylation of ZEBRA at S186 by protein kinase C (PKC) activated the protein (M. Baumann, H. Mischak, S. Dammeier, W. Kolch, O. Gires, D. Pich, R. Zeidler, H. J. Delecluse, and W. Hammerschmidt, J. Virol 72:8105-8114, 1998). Two residues of ZEBRA, T159 and S186, which fit the consensus for phosphorylation by PKC, were phosphorylated in vitro by this enzyme. Several isoforms of PKC (α, β(1), β(2), γ, δ, and ɛ) phosphorylated ZEBRA. All isoforms that phosphorylated ZEBRA in vitro were blocked by bisindolylmaleimide I, a specific inhibitor of PKC. Studies in cell culture showed that phosphorylation of T159 was not required for disruption of latency in vivo, since the T159A mutant was fully functional. Moreover, the PKC inhibitor did not block the ability of ZEBRA expressed from a transfected plasmid to activate the BMRF1 downstream gene. Of greatest importance, in vivo labeling with [(32)P]orthophosphate showed that the tryptic phosphopeptide maps of wild-type ZEBRA, Z(S186A), and the double mutant Z(T159A/S186A) were identical. Although ZEBRA is a potential target for PKC, in the absence of PKC agonists, ZEBRA is not constitutively phosphorylated in vivo by PKC at T159 or S186. Phosphorylation of ZEBRA by PKC is not essential for the protein to disrupt EBV latency.